Skeletal oxygen and carbon isotope compositions of Acropora coral primary polyps experimentally cultured at different temperatures. (14th July 2014) - Nishida, Kozue; Ishikawa, Kei; Iguchi, Akira; Tanaka, Yasuaki; Sato, Mizuho; Ishimura, Toyoho; Inoue, Mayuri; Nakamura, Takashi; Sakai, Kazuhiko; Suzuki, Atsushi
Abstract We investigated temperature and growth‐rate dependency of skeletal oxygen and carbon isotopes in primary polyps of Acropora digitifera (Scleractinia: Acroporidae) by culturing them at 20, 23, 27, or 31°C. Calcification was most rapid at 27 and 31°C. We obtained a δ18O‐temperature relationship (−0.18‰ °C−1) consistent with reported ranges for Porites, indicating that juvenile Acropora polyps can be used for temperature reconstruction. A growth‐rate dependency of skeletal isotopes was detected in the experimental polyps cultured at lower water temperatures, when the skeletal growth rate of these polyps was also low. The estimated upper calcification flux limit for a kinetic isotope effect to be observed in the δ18O‐growth rate relationship (∼0.4–0.7 g CaCO3 cm−2 yr−1) was similar to the calcification flux in Porites corresponding to a linear extension rate of 5 mm yr−1, the maximum rate at which the kinetic isotope effect is evident. This result suggests that the calcification flux can be used as a measure of growth rate‐related isotope fractionation, that is, the kinetic isotope effect, in corals of different genera and at different growth stages.